QCD equation of state via the complex Langevin method - Attanasio, Felipe; Jäger, Benjamin; Ziegler, Felix P. G. (Arxiv, 2022)
We present lattice simulations on the phase diagram of Quantum Chromodynamics (QCD) with two light quark flavours at finite chemical potential μ. To circumvent the sign problem we use the complex Langevin method. In this study, we have carried out finite density lattice computations for a pion mass of ∼ 480 MeV. We report on the pressure, energy and entropy equations of state in ab-initio lattice QCD calculations, as well as the observation of the Silver Blaze phenomenon.